Synthesis, characterisation and ethylene polymerisation performance of silyl bridged peralkylated bis(indenyl) zirconocenes - Angpanitcharoen, P; Lamb, JV; Turner, ZR; Buffet, J-C; O'Hare, D (Elsevier, 2020)
Six new peralkylated bis(indenyl) zirconocene complexes have been synthesised and fully characterised; rac-Me2SB(3-EtI*)ZrX2 and meso-Me2SB(3-EtI*)ZrX2 (X = Cl, Br and CH2Ph). Solution-phase ethylene polymerisation using rac-Me2SB(3-EtI*)ZrCl2/methylaluminoxane (MAO) and slurry-phase ethylene polymerisation using rac-Me2SB(3-EtI*)ZrCl2 immobilised on solid polymethylaluminoxane (sMAO), MAO modified layered double hydroxide (LDHMAO) and MAO modified silica (SSMAO) were studied. Polymerisation conditions were optimised for sMAO-rac-Me2SB(3-EtI*)ZrCl2 and applied to the other catalysts. A 75:25 mixture of rac- and meso-Me2SB(3-EtI*)Zr(CH2Ph)2 supported on sMAO showed the highest polymerisation activities (4832 kgPEmolZr−1 h−1 bar−1 at 60 °C), producing high density polyethylenes (HDPE) with modest molecular weights (Mw of 336 kg mol−1 at 60 °C) and molecular weight distributions (Mw/Mn) less than 3.2. sMAO-rac-Me2SB(3-EtI*)ZrCl2 was found to be responsive to H2 in a high-throughput screening system, producing polyethylenes with low molecular weights (Mw of 41 kg mol−1 with 1.6% H2). In the same high-throughput system, slurry-phase ethylene polymerisation in the presence of 1-hexene comonomer was shown to increase the polymerisation activity of sMAO-rac-Me2SB(3-EtI*)ZrCl2) compared to polymerisation in the same system without 1-hexene.